2014
DOI: 10.1371/journal.pone.0085766
|View full text |Cite
|
Sign up to set email alerts
|

Targeting GRP75 Improves HSP90 Inhibitor Efficacy by Enhancing p53-Mediated Apoptosis in Hepatocellular Carcinoma

Abstract: Heat shock protein 90 (HSP90) inhibitors are potential drugs for cancer therapy. The inhibition of HSP90 on cancer cell growth largely through degrading client proteins, like Akt and p53, therefore, triggering cancer cell apoptosis. Here, we show that the HSP90 inhibitor 17-AAG can induce the expression of GRP75, a member of heat shock protein 70 (HSP70) family, which, in turn, attenuates the anti-growth effect of HSP90 inhibition on cancer cells. Additionally, 17-AAG enhanced binding of GRP75 and p53, resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…demonstrated that 17‐AAG could sensitize Bcl‐2 inhibitor (−)‐gossypol through inhibiting ERK‐mediated autophagy and Mcl‐1 accumulation in Hep3B and HepG2 cells . Furthermore, 17‐AAG treatment induces the expression of 75 kDa glucose‐regulated protein (GRP75), which in turn decreases the efficacy of HSP90 inhibition on HCC cells . Dual targeting of GRP75 and HSP90 with MKT‐077 and 17‐AAG indicates synergistic effects on tumor growth in vivo .…”
Section: Targeting Hsps In Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated that 17‐AAG could sensitize Bcl‐2 inhibitor (−)‐gossypol through inhibiting ERK‐mediated autophagy and Mcl‐1 accumulation in Hep3B and HepG2 cells . Furthermore, 17‐AAG treatment induces the expression of 75 kDa glucose‐regulated protein (GRP75), which in turn decreases the efficacy of HSP90 inhibition on HCC cells . Dual targeting of GRP75 and HSP90 with MKT‐077 and 17‐AAG indicates synergistic effects on tumor growth in vivo .…”
Section: Targeting Hsps In Hccmentioning
confidence: 99%
“…Furthermore, 17‐AAG treatment induces the expression of 75 kDa glucose‐regulated protein (GRP75), which in turn decreases the efficacy of HSP90 inhibition on HCC cells . Dual targeting of GRP75 and HSP90 with MKT‐077 and 17‐AAG indicates synergistic effects on tumor growth in vivo . Another HSP90 inhibitor, 17‐(dimethylaminoethylamino)−17‐demethoxygeldanamycin (17‐DMAG), exhibits about two times potency against human HSP90 than 17‐AAG.…”
Section: Targeting Hsps In Hccmentioning
confidence: 99%
“…This current study suggests UBXN2A binds to mortalin's protein binding pocket and interferes with mortalin's binding partners (Dundas et al 2005;Gestl and Anne Bottger 2012;Guo et al 2014;Sadekova et al 1997) resulting in inactivation of mortalin oncoprotein in cancer cells. Part of the apoptotic resistance of cancer cells is mediated by activation of WT-mortalin in cancer cells, including osteosarcoma (Wadhwa et al 2015).…”
Section: Discussionmentioning
confidence: 58%
“…We hypothesized that UBXN2A binding to mortalin's binding pocket can also disrupt mortalin's interaction with partners, antagonize oncogenic function of mortalin, and eventually induce cell cytotoxicity in cancer cells. Overexpression of mortalin correlates with a higher proliferation rate, colony forming efficacy, motility, and tumor forming capacity; poor survival; and increased resistance to therapies (Dundas et al 2005;Gestl and Anne Bottger 2012;Guo et al 2014;Sadekova et al 1997). …”
Section: Ubxn2a Interferes With Cell Proliferation and Migration Of Cmentioning
confidence: 99%
“…MKT‐077 could bind to the NBD tail of mortalin resulting in tertiary structural modifications in the protein, attenuating its chaperone function. It also could destabilize the ATP‐bound conformation of mortalin . Moreover, it has been found that MKT‐077 occupies a pocket adjacent to the nucleotide‐binding cleft of Hsc70 and exerts a pseudo‐ADP bound conformer .…”
Section: Hsp70 and Crcmentioning
confidence: 99%